“An Empirical study on Enhancing Employee Engagement and Job Performance through Self-Determination Theory: The Role of Artificial Intelligence in Karnataka’s Banking Sector” - Arokiyaswamy C Milagrin Mary; Rathod Pralhad; Aishwaryalaxmi N.S.; Kagawade Shivanand (ITM Web of Conferences)
The The integration of Self-Determination Theory and Artificial Intelligence in facilitating employee engagement in job performance within the banking sector in Karnataka was explored. SDT states that three innate psychological needs are at the center of developing intrinsic motivation and job satisfaction, which is stated as autonomy, competence, and relatedness. When AI tools are designed to meet these needs, organizations can create a more supportive and motivating work environment. Examples are personalized experiences provided by AI in task management systems that better help employees manage their work, real-time feedback to develop employee skills, and collaboration platforms that enhance connections among team members. The outcome can be increased employee engagement and job satisfaction to enhance overall performance. It offers some practical insights into how AI can be used to respond to the recent challenges that emerge with regard to employee engagement within an increasingly fast-moving banking environment and further opines that there is a need to balance technology approaches with human-centered approaches. This will be quite useful for the HR manager and the organizational leader in driving motivation, productivity, and job satisfaction through AI.